Hybrid organic nanocrystal/carbon nanotube film electrodes for air- and photo-stable perovskite photovoltaics. Issue 8 (11th February 2019) - Siram, Raja Bhaskar Kanth; Khenkin, Mark V.; Niazov-Elkan, Angelica; K. M., Anoop; Weissman, Haim; Katz, Eugene A.; Visoly-Fisher, Iris; Rybtchinski, Boris
Abstract : Perylenediimide/carbon nanotube films solution-fabricated in air were used as back contacts for CsPbBr3 solar cells resulting in excellent outdoor performance. Abstract : We report on utilizing free-standing hybrid perylenediimide/carbon nanotube (PDI/CNT) films fabricated in air as back contacts for fully inorganic perovskite solar cells (glass/FTO/dense TiO2 /mesoporous TiO2 /CsPbBr3 /back electrode). The back contact electrode connection is performed by film transfer rather than by vacuum deposition or by wet processing, allowing the formation of highly homogeneous contacts under ambient conditions. The use of this novel electrode in solar cells based on CsPbBr3 resulted in efficiency of 5.8% without a hole transporting layer; it is significantly improved in comparison to the reference cells with standard gold electrodes. Overall device fabrication can be performed on air, using inexpensive processing methods. The hybrid film electrodes dramatically improve the cell photo-stability under ambient conditions and under real-life operating conditions outdoors. The champion unencapsulated device demonstrated less than 30% efficiency loss over 6 weeks of outdoor aging in Negev desert conditions. The CNT/PDI electrodes offer the combination of fabrication simplicity, unique contacting approach, high efficiency and good operational stability for perovskite photovoltaics.